2019
DOI: 10.12659/msm.916292
|View full text |Cite|
|
Sign up to set email alerts
|

Long Noncoding RNA TP73-AS1 Targets MicroRNA-329-3p to Regulate Expression of the SMAD2 Gene in Human Cervical Cancer Tissue and Cell Lines

Abstract: Departmental sources Background: Worldwide, mortality from cervical cancer in women remains high. This study aimed to investigate the expression of long noncoding RNA (lncRNA) TP73-AS1, microRNA-329-3p (miRNA-329-3p), and the SMAD2 gene and their regulatory relationships in human cervical cancer tissue and cervical cancer cell lines. Material/Methods: Cervical cancer tissue samples (n=30) and normal control cervical tissues were studied. Cell proliferation and migration were investigated in HeLa and SiHa human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…In our research, we predicted the ceRNA network of PCAT1 and Netrin-1 through biometric analysis and found that PCAT1-miR-329-3p-Netrin-1 can form a ceRNA network. miR-329-3p has been found to be negatively correlated with cancer development in a variety of cancers [30][31][32]. On this basis, we further confirmed that PCAT1 can affect the Netrin-1-CD146 complex by regulating miR-329-3p, thus affecting the EMT process and liver metastasis process of colorectal cancer.…”
Section: Introductionsupporting
confidence: 77%
“…In our research, we predicted the ceRNA network of PCAT1 and Netrin-1 through biometric analysis and found that PCAT1-miR-329-3p-Netrin-1 can form a ceRNA network. miR-329-3p has been found to be negatively correlated with cancer development in a variety of cancers [30][31][32]. On this basis, we further confirmed that PCAT1 can affect the Netrin-1-CD146 complex by regulating miR-329-3p, thus affecting the EMT process and liver metastasis process of colorectal cancer.…”
Section: Introductionsupporting
confidence: 77%
“…Interestingly, novel-320 was upregulated in both the MM_F_A vs. ww_F_A and MM_F_A vs. MM_L_A comparisons, indicating that novel-302 regulates its targets to influence high fertility and transform the follicle phase to the luteal phase in the adrenal glands of sheep. Researchers have found that miR-329b-3p can inhibit the proliferation and growth of tumor cells [35][36][37][38][39]. miR-329b-3p was downregulated in both the ww_F_A vs. ww_L_A and MM_L_A vs. ww_L_A comparisons, which illustrated that negative regulation was possible in the adrenal glands at the follicle phase and further regulated the high fertility of the FecB ++ sheep.…”
Section: Discussionmentioning
confidence: 95%
“…6 LncRNA TP73-AS1 targets miR-329-3p to regulate expression of SMAD2 in human cervical cancer tissue and cell lines. 7 Dysregulations of lncRNAs in HCC have been revealed in several previous investigations. Upregulation of lncRNA SNHG16 inhibits HCC cell proliferation and chemoresistance via sponging miR-93.…”
Section: Introductionmentioning
confidence: 94%